Analysis of Feminist Values in The Movie 'Suffragette' (2015): Liberal Feminist by Mary Wollstonecraf - Dewi Pingkan Kango; Rusni Podungge; Novi Rusnarty Usu (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze feminist values in the film Suffragette (2015) through the lens of liberal feminism using Mary Wollstonecraft’s theory. Employing a qualitative method, the researcher examines dialogues, character actions, and the film’s script to interpret the representation of women's roles, resistance, and struggle for equality in a patriarchal society. The study uses a sociology of literature approach, positioning the film as a reflection of historical and socio-cultural realities. The analysis focuses on how liberal feminist ideals—particularly Equal Liberty, Gender Justice, and Mono-Androgyny—are embedded in the narrative and character development. From 15 selected scenes, 6 reflect Equal Liberty, showing the characters’ demands for equal political rights and participation. Seven scenes demonstrate Gender Justice, highlighting women's fight against discrimination in wages, work, and societal norms. Two scenes portray Mono-Androgyny, depicting women who transcend traditional gender roles and assert their autonomy. The findings suggest that Suffragette effectively visualizes the core principles of liberal feminism, especially those advocated by Wollstonecraft, by showing women's pursuit of fairness, independence, and legal recognition. This research offers a fresh perspective on feminist film analysis and underscores the continuing relevance of liberal feminist values in both historical and contemporary contexts.